Measuring Intercultural Sensitivity Among Pre-Service Teacher Students in Multicultural Higher Education Context - Firdaus, Laras; Dewi, Ika Nurani (Faculty of Engineering and Applied Science, 2026)
This study aimed to measure the level of intercultural sensitivity (IS) among pre-service teachers at Universitas Pendidikan Mandalika. The research employed a cross-sectional quantitative survey design involving 109 first-year pre-service teachers (43 males; 66 females; mean age = 18.52 years) from Sasak, Sumbawa, Bima, and NTT ethnic backgrounds. The instrument used was the Intercultural Sensitivity Scale (ISS; 24 items; five dimensions), with analyses including validity and reliability testing, descriptive statistics, normative classification (mean ± 1 SD), and one-way ANOVA. The results indicated that two items (18 and 24) were invalid, while the overall reliability of the instrument was high (Spearman–Brown = 0.864). Based on normative classification, most participants were categorized at a moderate level of IS (72.48%), followed by high (15.60%) and low (11.93%) categories. Sub-scale analysis revealed that interaction attentiveness had the highest mean score (3.23), whereas interaction enjoyment and interaction confidence were relatively the lowest (3.13). Comparative tests showed no significant differences based on gender or ethnicity across all sub-scales. These findings suggest that pre-service teachers possess a relatively positive affective foundation toward intercultural interaction. However, further strengthening is still needed, particularly in the dimensions of interaction enjoyment and interaction confidence in intercultural engagement. Further elaboration of this study can be found in the limitations and recommendations section.